Performance Comparison Between LDR and Phototransistor Sensor for Dual-Axis Sun Tracker Sensor Based on Tetrahedron Geometry - Hari Anna Lastya; Yuwaldi Away; Tarmizi Tarmizi; Ira Devi Sara; M Ikhsan; Ulya Zikra; Nikmal Maula Mirda (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2023)
Solar energy is optimally obtained by solar cells when the solar cells are perpendicular to the sun's position, so a sun tracker is needed to track the sun precisely. This research compares the electrical power used in two system dual-axis sun trackers with a tetrahedron geometry that uses an LDR sensor with a phototransistor sensor. The two sun trackers are built identically and the experimental data with the servo movement and the solar cell load are carried out side by side. The servo motor controls with Proportional Integral Derivative (PID) algorithm controls the movement of the dual-axis sun tracker. Data were obtained by recording the voltage and current received by the solar cells installed on the two sun trackers and comparing the results. The results showed that the phototransistor sensor performs better than the LDR sensor. This can be seen from the amount of power generated by the phototransistor sensor which is more than the power generated by the LDR sensor on the solar cell. The solar energy received by sun tracker uses a phototransistor sensor average 40% more than sun tracker uses an LDR sensor